2012
DOI: 10.1271/bbb.120235
|View full text |Cite
|
Sign up to set email alerts
|

Consumption ofPuerariaFlower Extract Reduces Body Mass Indexviaa Decrease in the Visceral Fat Area in Obese Humans

Abstract: In Japan, kudzu is a familiar plant, well-known as an ingredient in the Japanese-style confections kudzu-kiri and kudzu-mochi. In this study, we focused on the flower of kudzu (Pueraria thomsonii) and conducted a clinical trial to investigate the effects of Pueraria thomsonii flower extract (PFE) on obesity using obese Japanese males and females (BMI ≥ 25 kg/m(2)). Eighty-one obese subjects were randomly divided into three groups and consumed test food containing 300 mg of PFE, 200 mg of PFE, and a placebo ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…In several studies, 12-24-week-periods have been used to assess decreases in AVAT 18,19) . Furthermore, an increase in adiponectine and a decrease in highsensitivity C-reactive protein (CRP) have been induced by a three-month regimen of oral EPA 20) .…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, 12-24-week-periods have been used to assess decreases in AVAT 18,19) . Furthermore, an increase in adiponectine and a decrease in highsensitivity C-reactive protein (CRP) have been induced by a three-month regimen of oral EPA 20) .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the no observed adverse effect level of PFE in SD rats was concluded to be the dose equivalent to 5.0%, as a dietary mixture under the present study conditions. Moreover, regarding PFE intake per body weight, as described above, the human equivalent dose of PFE was estimated using the body weight and body surface area to be 180 and 29.2 g/d, respectively, in men (60 kg), and 175 and 28.4 g/d, respectively, in women (50 kg) (Reagan‐Shaw and others ), which are much higher than the PFE efficacy dose for anti‐obesity of 300 mg/d, reported in our previous work (Kamiya and others ).…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, we conducted 2 clinical trials in mildly obese humans to evaluate the anti‐obesity effect of PFE, in which an oral intake of 300 mg of PFE per day for 12 wk reduced both body weight (BW) and fat area. In addition, there were no changes of clinical significance in hematological, biochemical blood, and urinary analyses, and no serious adverse effects were observed during either test period (Kamiya ; Kamiya ).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In China, tea made from dried Kudzu flowers is widely consumed [1], and PFE is consumed as a nutritional supplement for the treatment of hangovers and obesity in Japan. We previously reported that PFE exerts anti-obesity effects in humans and mice fed high-fat diets [2][3][4]. In addition, we also reported that the isoflavone-rich fraction of dietary PFE exhibits anti-obesity effect in mice fed high-fat diets [5].…”
Section: Introductionmentioning
confidence: 85%